The history of Tur Abdin - Ignatios Aprem I. Antiochien, Patriarch 1887-1957; Moosa, Matti 1924-2014 (Piscataway, NJ Gorgias Press [u.a.], 2008)
Translator's introduction -- Sources of this book -- Boundaries of the mountain (Tur Abdin), its people and name -- The introduction of Christianity to Tur Abdin -- Ascetics who flourished in the mountain (Tur Abdin) -- Fortresses of Tur Abdin -- Towns and villages of Tur Abdin -- Churches of Tur Abdin -- Monasteries of Tur Abdin -- The monastery of Qartmin -- Other patriarchs and maphrians of Tur Abdin -- Outstanding native bishops of Tur Abdin -- Bishops who flourished in Tur Abdin -- Bishops of Tur Abdin who sat in Hah -- Bishops of the monastery of Qartmin after the split of the diocese -- Native bishops of Tur Abdin who administered other dioceses -- Bishops of Tur Abdin in different times -- Bishops of other dioceses who came from Tur Abdin -- Patriarchs of Tur Abdin -- Illegitimate patriarch who sat in Tur Abdin, they are : Maphrians of Tur Abdin -- Bishops ordained by patriarchs of Tur Abdin each during his patriarchate -- Accounts of Syrian Church historians about the monastery of Qartmin -- Account of the historian monk of Qartmin -- Accounts of some ascetics, pious and venerable men who flourished in the monastery of Qartmin -- Account of the anonymous history published by Propus whose copy is in London no. 624/14 -- Account of Bar Hebraeus in his ecclesiastical history, part I -- Account of the historian Rabban Yeshu', Abbot of the Monastery of Qartmin (ascribed to Mar Dionysius Tall Mahre) -- Accounts we copied from the book of life of the monastery of Qartmin -- Books of the monastery's (of Qartmin) -- Other misfortunes which afflicted the monastery of Qartmin -- Accounts of Syrian historians about the affairs of Tur Abdin -- Account of Bar Hebraeus in his Syriac history -- Account of the historian Mar Mikhai'l al-Kabir (Michael Rabo, the Syrian) -- Account of the anonymous cleric of Edessa -- Account of the priest Addai of Basibrina around the year 1500 A.D., appended to the history of the learned Bar Hebraeus -- Travel of the priest Addai of Basibrina -- The warfare of Timur Khan (Tamerlane) in Tur Abdin taken from another copy -- The village of Basibrina -- Miscellaneous chronicles on Tur Abdin derived from ancient Syriac manuscripts preserved in churches and monasteries -- The Monastery of Mar Yaqub the Hermit in Salah -- The Monastery of Mar Gabriel (Qartmin) -- The Monastery of Mar Malke -- The Monastery of the Cross in Atafiya -- The Monastery of Mar Awgen -- The Monastery of Mar Sharbil -- Church of the Virgin in Midyat and other churches -- Ancient Syriac inscriptions in Tur Abdin on stones, tombs (epitaphs) and front doors of churches and monasteries -- The monastery of Qartmin -- The church of Mar Azazel in the village of Kafar ze -- The Church of Mar Cyriacus in Arnas -- The Church of Basibrina -- The Church of Hah -- The Church of Ishtarko (Heshtarke) -- The old Church of Mar Saba -- The ecession of Tur Abdin from the Apostolic see -- Dioceses of Tur Abdin -- Learned men and writers educated in Tur Abdin -- Syrian calligraphers of Tur Abdin -- Mar Shim'un (Simon) Zaytuni -- The family of Tuma Sharqi (Easterner) -- Family of the notable Saba of Basibrina -- The twelfth century 1110-1200? -- The Muhallamiyya -- Governors of Tur Abdin -- Ayyubid Kings (Lords) of Hisn Kifa -- Kurdish Bakhti rulers -- Manslaughter and devastation inflicted by Izz Al-Din Scher and Musawwar Beg in the year 1855 -- Warfare and calamities afflicting Tur Abdin -- Persecution of the Armeninas and Syrians in 1895 -- Vehement persecution (of the Christians) during world war I
Translator's introduction -- Sources of this book -- Boundaries of the mountain (Tur Abdin), its people and name -- The introduction of Christianity to Tur Abdin -- Ascetics who flourished in the mountain (Tur Abdin) -- Fortresses of Tur Abdin -- Towns and villages of Tur Abdin -- Churches of Tur Abdin -- Monasteries of Tur Abdin -- The monastery of Qartmin -- Other patriarchs and maphrians of Tur Abdin -- Outstanding native bishops of Tur Abdin -- Bishops who flourished in Tur Abdin -- Bishops of Tur Abdin who sat in Hah -- Bishops of the monastery of Qartmin after the split of the diocese -- Native bishops of Tur Abdin who administered other dioceses -- Bishops of Tur Abdin in different times -- Bishops of other dioceses who came from Tur Abdin -- Patriarchs of Tur Abdin -- Illegitimate patriarch who sat in Tur Abdin, they are : Maphrians of Tur Abdin -- Bishops ordained by patriarchs of Tur Abdin each during his patriarchate -- Accounts of Syrian Church historians about the monastery of Qartmin -- Account of the historian monk of Qartmin -- Accounts of some ascetics, pious and venerable men who flourished in the monastery of Qartmin -- Account of the anonymous history published by Propus whose copy is in London no. 624/14 -- Account of Bar Hebraeus in his ecclesiastical history, part I -- Account of the historian Rabban Yeshu', Abbot of the Monastery of Qartmin (ascribed to Mar Dionysius Tall Mahre) -- Accounts we copied from the book of life of the monastery of Qartmin -- Books of the monastery's (of Qartmin) -- Other misfortunes which afflicted the monastery of Qartmin -- Accounts of Syrian historians about the affairs of Tur Abdin -- Account of Bar Hebraeus in his Syriac history -- Account of the historian Mar Mikhai'l al-Kabir (Michael Rabo, the Syrian) -- Account of the anonymous cleric of Edessa -- Account of the priest Addai of Basibrina around the year 1500 A.D., appended to the history of the learned Bar Hebraeus -- Travel of the priest Addai of Basibrina -- The warfare of Timur Khan (Tamerlane) in Tur Abdin taken from another copy -- The village of Basibrina -- Miscellaneous chronicles on Tur Abdin derived from ancient Syriac manuscripts preserved in churches and monasteries -- The Monastery of Mar Yaqub the Hermit in Salah -- The Monastery of Mar Gabriel (Qartmin) -- The Monastery of Mar Malke -- The Monastery of the Cross in Atafiya -- The Monastery of Mar Awgen -- The Monastery of Mar Sharbil -- Church of the Virgin in Midyat and other churches -- Ancient Syriac inscriptions in Tur Abdin on stones, tombs (epitaphs) and front doors of churches and monasteries -- The monastery of Qartmin -- The church of Mar Azazel in the village of Kafar ze -- The Church of Mar Cyriacus in Arnas -- The Church of Basibrina -- The Church of Hah -- The Church of Ishtarko (Heshtarke) -- The old Church of Mar Saba -- The ecession of Tur Abdin from the Apostolic see -- Dioceses of Tur Abdin -- Learned men and writers educated in Tur Abdin -- Syrian calligraphers of Tur Abdin -- Mar Shim'un (Simon) Zaytuni -- The family of Tuma Sharqi (Easterner) -- Family of the notable Saba of Basibrina -- The twelfth century 1110-1200? -- The Muhallamiyya -- Governors of Tur Abdin -- Ayyubid Kings (Lords) of Hisn Kifa -- Kurdish Bakhti rulers -- Manslaughter and devastation inflicted by Izz Al-Din Scher and Musawwar Beg in the year 1855 -- Warfare and calamities afflicting Tur Abdin -- Persecution of the Armeninas and Syrians in 1895 -- Vehement persecution (of the Christians) during world war I
Includes index
Archivierung prüfen
Keywords: Syrian Orthodox Church -- Turkey -- Ṭur ʿAbdin -- History; Syrian Orthodox Church -- History -- Turkey -- Ṭur ʿAbdin; Syriac Christians -- Turkey -- Ṭur ʿAbdin -- History; Monasteries, Syrian Orthodox -- Turkey -- Ṭur ʿAbdin; Monasticism and religious orders, Syrian Orthodox -- Turkey -- Ṭur ʿAbdin; Syriac Christians -- History -- Turkey -- Ṭur ʿAbdin; Ṭur ʿAbdin (Turkey) -- Church history; Ṭur ʿAbdin (Turkey) -- History